JURNALISTIK RINTISAN NABI MUHAMMAD SAW - Kartini (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2018)
Prophet Muhammad SAW, has used the treatise as his own communication media, where he is a illiterate (Ummi). Even so, preach in treatise (correspondence) was still carried out with the help of the Prophet's friend who was a good writer. 12 Early Rabiul of elephant is the date of the birth of the Prophet Muhammad Subhanahu wata'ala. However, behind the history, if we trace deeper, it turns out that the carrier of Islam is a journalist and even pioneering journalism on this earth. From the activities of the prophet and the companions who carried out to preach in writing, especially those addressed to the kings showed that the foundation of journalism and the press had been laid depend on the conditions and progress of the people at that time.